Evaluasi Sistem Pengolahan Limbah Air Domestik: Tinjauan Teknis dan Lingkungan di Kelurahan Bulukunyi, Palongbangkeng Selatan, Takalar - Adonk, Lutfi Hair Djunur (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
Improving access to adequate sanitation is an essential step in reducing environmental pollution and the risk of waterborne diseases, particularly in areas with limited sanitation facilities. This study aims to enhance sanitation access in Bulukunyi Subdistrict, Takalar Regency, through the construction of individual sanitation facilities, including toilets, septic tanks, soak pits, and grease traps, for the management of domestic wastewater (blackwater). The implementation method was divided into three stages: the preparation stage (literature review, beneficiary survey, and site determination), the implementation stage (technical assistance during facility construction), and the evaluation stage (monitoring the utilization of the facilities). A total of 39 households benefited from this program. The evaluation results indicate that the facilities functioned as intended and had a positive impact on the community’s clean and healthy living behaviors, although some beneficiaries had not yet permanently sealed their septic tanks and soak pits. This initiative demonstrates that providing adequate sanitation facilities, along with technical guidance and education, can be an initial step toward sustainable domestic wastewater management at the household level.